Proposal of A VCSEL Datasheet Model for Optical Systems simulations - AGOSSOU, Carlos M.; DJOGBE, LÉOPOLD; SANYA, MAX FREJUS O.; SOTINDJO, Patrick; VIANOU, COKOU ANTOINE; AUPETIT-BERTHELEMOT, Christelle (My University, 2018)
With the proliferation of voracious bandwidth- intensive multimedia applications, deployed optical sources within optical LANs in data centers must transmit data at very high data rates over short ranges and at a lower cost. To do this, among several optical sources, Vertical Cavity Surface Emitting Laser (VCSEL) is most often used. In this work, we have developed a cosimulation laser model between OptiSystem 7 and Matlab for much more realistic simulations of VCSEL-based links, such as the case of transmission systems within these data centers. After some tests of the modeled component, the chirp phenomena were validated as well as current-power characteristic and component frequency response.
Keywords: LAN networks; data center; phenomenological model.